Recombinant lactobacillin PlnK adjusts the gut microbiome distribution in broilers. Issue 4 (3rd July 2020) - Xu, L.; Zhou, J.; Qu, G.; Lin, Z.; Fan, Q.; Wang, C.; Wang, Q.
ABSTRACT: 1. The heterologous expression and biological function of the Lactobacillus bacteriocin plantaricin K (PlnK) remain largely unknown. 2. In this study, PlnK was efficiently expressed in competent E. coli BL21 (used in transformation and protein expression) after 12 h, at 37°C and in 0.4 mmol/l isopropyl β- d-1-thiogalactopyranoside (IPTG). 3. The inhibitory bacterial spectrum of recombinant PlnK was investigated and indicated that levels of PlnK above 0.10 mg/ml produced an obvious inhibitory effect on gram-positive bacteria and gram-negative bacteria in vitro . 4. The effects of PlnK on intestinal immune function and the gut microbiome distribution in broilers were studied. The results revealed that, after consuming 2.50 × 10 ˗3  mg/ml of PlnK in water for one week, at the phylum level, the abundance of Firmicutes was increased and the abundance of Bacleroidetes was decreased. At the family level, the abundance of  Lachnospiraceae, Ruminococcaceae  and  Streptococcaceae  were significantly improved, but the abundance of  Bacteroidaceae  was reduced. At the genus level, the abundances of Lachnoclostridium, Streptococcus and Ruminococcaceae -UCG-013, were significantly up-regulated, and the abundance of Bacteroides was down-regulated. 5. After oral liquid intake of PlnK for one week, levels of secretory immunoglobulin A (sIgA) in the duodenal mucus were not significantly increased, but the mRNA levels of TLR 3, MDA 5, IFN-α, IFN-β, IFITM 3 and IFITM 10 in the duodenum were significantly reduced. 6. This study demonstrated that the recombinant PlnK could adjust the intestinal microbiome distribution and downregulate the IFN pathway.